HUBUNGAN SELF EFFICACY DAN KEMAMPUAN MEMBACA SISWA KELAS III SD - Hanhan Hindasyah; Wikanengsih Wikanengsih; Wiwin Yuliani Wiwin Yuliani (IKIP Siliwangi, 2018)
Research on the relationship of self efficacy and reading ability of students in grade III SD 1 Suci Kaler supports understanding the relationship between self efficacy and reading ability. The research method uses quantitative correlational. Data collection in this study uses self efficacy questionnaires and secondary data on students' reading skills scores. The study population was all students of class III SD 1 Suci Kaler with a research sample of 52 people. The data analysis technique used is the correlational hypothesis test with the product moment test with the help of the SPSS 22 application. Based on the results of the study related to the relationship of self efficacy and reading skills of third grade students of SD 1 Suci Kaler with a correlation value of 0.403, it can be interpreted between self efficacy and skills reading grade III students at SD 1 Suci Kaler is positive, meaning that if self-efficacy can increase, students' reading skills will immediately increase. The level of conversation between self-efficacy and reading skills of third grade students at SD 1 Suci Kaler depends on the medium category.Keywords: Self-efficacy, reading skills.